2022
DOI: 10.1007/s42757-021-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Soot: A review of computational models at different length scales

Abstract: The computational modelling of soot formation and destruction during the combustion process is one of the most challenging topics in combustion research. This paper reviews the numerical soot models constructed at different length scales, including macroscale, mesoscale, and microscale. The four key stages of soot evolution, including nucleation, surface growth and coagulation, agglomeration, and oxidation, are first described with the generally accepted mathematical formulations in each stage explained. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…The moment transformation method offers a robust mathematical approach that simplifies the analysis and calculation process, enabling an efficient and accurate solution to the equation. − The moment transformation method regresses the model’s parameters using corresponding moments from system analysis to match the experimental data’s moments for the system output variables …”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…The moment transformation method offers a robust mathematical approach that simplifies the analysis and calculation process, enabling an efficient and accurate solution to the equation. − The moment transformation method regresses the model’s parameters using corresponding moments from system analysis to match the experimental data’s moments for the system output variables …”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…𝜎/ √ 𝑛 (6) Figure 6 presents the results obtained for the significance level of engine speed and torque as a function of the p-value, incorporating mass flow, temperature, and concentrations of PN23 and PN10 before and after the TWC for all evaluated steady-state modes. Firstly, it is observed that both parameters are directly correlated with the mass flow rate and exhaust gas temperature, as evidenced by their p-values being lower than 0.05.…”
Section: 𝑡 𝑥̅ 𝜇mentioning
confidence: 99%
“…Additionally, urban air pollution was linked to nearly six and seven million premature deaths in 2019 [3]. The transportation sector, in particular, is a major source of urban air pollution, contributing to 56% of carbon monoxide (CO) emissions, 44% of nitrogen oxides (NOx), 31% of unburned hydrocarbons (UHC) [4], and 41% of ultrafine particle numbers (PN) [5], whose formation includes stages like pyrolysis, nucleation, coagulation agglomeration, and oxidation [6], which at the same time are affected by interactions with the environment when the particles are flowing in the near-wall region, as well as in the whole flow field [7]. In response, governments worldwide have established regulations to limit emissions from combustion engines in vehicles using standards like the 2 of 16 Euro for the European Union, EPA for the USA, PNLT for Japan, BSES for India, and China for China [8].…”
Section: Introductionmentioning
confidence: 99%
“…Soot, also known as black carbon, can cause serious health issues , and acts as a major forcing factor in climate change. , The exact mechanism of the formation of soot particulates from gaseous precursors is still unknown due to the complex chemical nature of the hydrocarbon reaction network and time- and length-scale of the soot formation processes. According to the present understanding, soot formation occurs by a series of complex physicochemical events such as the formation of gas-phase soot precursors (including, but not limited to, polycyclic aromatic hydrocarbons or PAHs), nucleation of incipient soot particles, growth and maturation of incipient soot particles due to surface reactions, aggregation by coagulation or coalescence, and decay of the particles by fragmentation and oxidation. − The inception of soot particles is arguably the least understood phenomenon among these processes, and the exact chemical reaction pathways of soot inception are not completely known yet. Researchers agree that soot formation starts with production of small gas-phase precursor molecules such as acetylene, which leads to PAHs like benzene, pyrene, and coronene. − These freshly formed PAHs then combine to form the solid or liquid-like incipient soot particles. − These particles then start to grow by surface reactions and coalescence to form larger soot particles. ,− …”
Section: Introductionmentioning
confidence: 99%